The Green RM Practices and Their Impacts on the Corporate Image of Uae Organisations - HAFEZ, AHMAD AL (İstanbul Kültür Üniversitesi, 2023)
Green HRM, the practice of integrating a sustainability philosophy into not only human resource selection, promotion, and training but also into the working practices of employees therein, has remained a somewhat under-investigated subject matter. Specifically, the current work, through its methodological approach, has focused on assessing those green HRM practices that are used by clothing and retail organizations operating in the UAE; the effects of such on the corporate image of said companies; and the manner in which green HRM helps such businesses improve their corporate image.

Bir sürdürülebilirlik felsefesini yalnızca insan kaynakları seçimi, terfisi ve eğitimine değil, aynı zamanda buradaki çalışanların çalışma uygulamalarına da entegre etme uygulaması olan Yeşil İKY, yeterince araştırılmamış bir konu olarak kalmıştır. Spesifik olarak, mevcut çalışma, metodolojik yaklaşımı aracılığıyla BAE'de faaliyet gösteren giyim ve perakende kuruluşları tarafından kullanılan yeşil İKY uygulamalarını değerlendirmeye odaklanmıştır. Yeşil İKY'nin söz konusu şirketlerin kurumsal imajına etkileri ve yeşil İKY'nin bu tür işletmelerin kurumsal imajlarını geliştirmelerine nasıl yardımcı olduğu açıklanmaya çalışılmıştır.
Yeşil İKY Uygulamaları ve Birleşik Arap Emirlikleri (BAE) Organizasyonlarının Kurumsal İmajına Etkileri
▪ Yüksek lisans tezi.
Keywords: Green Human Resource Management; Corporate Image